关闭

HDU2554

75人阅读 评论(0) 收藏 举报
分类:

(ai-bi)=i+1

all(ai+bi) = (1+2n)2n/2

all(ai-bi)=(3+n)n/2

#include <iostream>
using namespace std;
/*
(b1+...+bn) = (n(n+3)/2 + 2n(2n+1)/2 )/2== (5n*n+5*n)/4 5n(n+1)/4
(a1+...+an) = ( 3n*n-n)/4   n(3n-1)/4
*/
int main(){
    int n ;
    while(cin >> n,n){
      if(n%4 == 0 || (n+1)%4 == 0 || (3*n-1)%4 == 0) cout <<"Y" <<endl ;
      else cout << "N" <<endl;
    }
    return 0;
}


0
0

查看评论
* 以上用户言论只代表其个人观点,不代表CSDN网站的观点或立场
    个人资料
    • 访问:12654次
    • 积分:776
    • 等级:
    • 排名:千里之外
    • 原创:67篇
    • 转载:2篇
    • 译文:0篇
    • 评论:0条